Rafał Łatka, Beata Mackiewicz, ks. Dominik Zamiatała, Prymas Stefan Wyszyński. Biografia - Mażewski, Lech (Czasopismo Prawno-Historyczne, 2021)
Rafał Łatka, Beata Mackiewicz, ks. Dominik Zamiatała, Prymas Stefan Wyszyński. Biografia